3D Microporous Base‐Functionalized Covalent Organic Frameworks for Size‐Selective Catalysis. (7th February 2014) - Fang, Qianrong; Gu, Shuang; Zheng, Jie; Zhuang, Zhongbin; Qiu, Shilun; Yan, Yushan
Abstract The design and synthesis of 3D covalent organic frameworks (COFs) have been considered a challenge, and the demonstrated applications of 3D COFs have so far been limited to gas adsorption. Herein we describe the design and synthesis of two new 3D microporous base‐functionalized COFs, termed BF‐COF‐1 and BF‐COF‐2, by the use of a tetrahedral alkyl amine, 1, 3, 5, 7‐tetraaminoadamantane (TAA), combined with 1, 3, 5‐triformylbenzene (TFB) or triformylphloroglucinol (TFP). As catalysts, both BF‐COFs showed remarkable conversion (96 % for BF‐COF‐1 and 98 % for BF‐COF‐2), high size selectivity, and good recyclability in base‐catalyzed Knoevenagel condensation reactions. This study suggests that porous functionalized 3D COFs could be a promising new class of shape‐selective catalysts.